Challenges in the treatment of a chronic disease: A study of narratives of people with juvenile myoclonic epilepsy. (August 2021) - Contier, Ana Teresa R.; Alonso, Neide Barreira; Araújo, Noemi S.; Taura, Mariângela; Cavalheiro, Esper A.
Highlights: Participants highlighted the impact of epilepsy on their families. Participants reported that difficulties were more intense at the beginning of treatment. Clinical support is essential to treatment adherence. Abstract: Purpose: The purpose of this study was to explore how people with juvenile myoclonic epilepsy perceive the impact of treatment. Methods: We conducted 14 interviews of participants with juvenile myoclonic epilepsy recruited with the support of the Brazilian Association of Epilepsy in 2018 in São Paulo. Thematic analysis was carried out by two investigators who independently coded the transcripts and reviewed the coding results to check for agreement. Results: Participants' ( n  = 14, 8 female) mean age was 31.4 years (SD ± 8.3) and their onset of seizures occurred at mean age 13.4 (SD ± 2.9). The answers to the interview questions revealed the paths of participants through life as they dealt with difficulties and challenges. Three interrelated themes and seven sub-themes emerged from the answers of the participants: seizure control, impact of epilepsy and attitude of others. Conclusion: This investigation may be useful in providing insights for the interventions of health providers in caring for people with JME. Themes and sub-themes that emerged from this study are connected to important aspects of treatment that go beyond focusing solely on seizures.